Preliminary study based on methylation and transcriptome gene sequencing of lncRNAs and immune infiltration in hypopharyngeal carcinoma - Wu, Kainan; Chang, Fen; Li, Wenming; Wei, Dongmin; Cao, Shengda; Xie, Yulin; Li, Ce; Lei, Dapeng (Frontiers in Oncology, 2023)
Background: Hypopharyngeal squamous cell cancer (HSCC) is one of the most malignant tumors of the head and neck. It is not easy to detect in the early stage due to its hidden location; thus, lymph node metastasis is highly likely at diagnosis, leading to a poor prognosis. It is believed that epigenetic modification is related to cancer invasion and metastasis. However, the role of m6A-related lncRNA in the tumor microenvironment (TME) of HSCC remains unclear. Methods: The whole transcriptome and methylation sequencing of 5 pairs of HSCC tissues and adjacent tissues were performed to identify the methylation and transcriptome profiles of lncRNAs. The biological significance of lncRNAs differentially expressing the m6A peak was analyzed by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes. By constructing an m6A lncRNA-microRNA network, the mechanism of m6A lncRNAs in HSCC was analyzed. The relative expression levels of selected lncRNAs were examined by quantitative polymerase chain reaction. The CIBERSORT algorithm was used to evaluate the relative proportion of immune cell infiltration in HSCC and paracancerous tissues. Results: Based on an in-depth analysis of the sequencing results, 14413 differentially expressed lncRNAs were revealed, including 7329 up-regulated and 7084 down-regulated lncRNAs. Additionally, 4542 up-methylated and 2253 down-methylated lncRNAs were detected. We demonstrated methylation patterns and gene expression profiles of lncRNAs of HSCC transcriptome. In the intersection analysis of lncRNAs and methylated lncRNAs, 51 lncRNAs with up-regulated transcriptome and methylation and 40 lncRNAs with down-regulated transcriptome and methylation were screened, and significantly differentiated lncRNAs were further studied. In the immune cell infiltration analysis, B cell memory was significantly elevated in cancer tissue, while γδT cell amount was significantly decreased. Conclusion: m6A modification of lncRNAs might be involved in HSCC pathogenesis. Infiltration of immune cells in HSCC might provide a new direction for its treatment. This study provides new insights for exploring the possible HSCC pathogenesis and searching for new potential therapeutic targets.